BS EN IEC 61300-3-46. Fibre optic interconnecting devices and passive components. Basic test and measurement procedures. Part 3-46. Examinations and Measurements. Bore diameter in rectangular ferrules (8th February 2023) - British Standards Institution,
No abstract available